Comparison of Outcomes of Pediatric Catheter Ablation by Anesthesia Strategy: A Report From the NCDR IMPACT Registry. (July 2021) - Janson, Christopher M.; Shah, Maully J.; Kennedy, Kevin F.; Iyer, V. Ramesh; Sweeten, Tammy L.; Glatz, Andrew C.; Steven, James M.; O'Byrne, Michael L.
Abstract : Background: Anesthesia strategies for pediatric ablation procedures include general anesthesia (GA) and monitored anesthesia care (MAC). The effects of anesthesia strategy on arrhythmia inducibility and procedural outcomes have not been investigated. Methods: A multicenter retrospective study was performed, using data from the National Cardiovascular Data Registry's Improving Pediatric and Adult Congenital Treatment Registry. Data from subjects 1 to 21 years undergoing elective first-time electrophysiology study (EPS) for evaluation of documented supraventricular tachycardia, ectopic atrial tachycardia, or premature ventricular contractions (PVC)/ventricular tachycardia (VT) from April 1, 2016, to December 31, 2019, were included, excluding cases with Wolff-Parkinson-White, congenital heart disease, and cardiomyopathy. The primary outcome was a negative EPS, defined as failure to induce the clinical tachyarrhythmia. Secondary outcomes included ablation success and adverse events. Results: Six thousand six hundred twenty-one subjects from 78 centers were evaluated: 49% male; mean age 13.3±3.8 years. GA was used in 5913 (89%), with MAC in 708 (11%). A negative EPS occurred in 9% of cases overall, with no difference by anesthesia strategy (9% GA versus 10% MAC, P =0.2). In supraventricular tachycardia and ectopic atrial tachycardia, there was no significant difference in likelihood of a negative EPS by anesthesia strategy. In PVC/VT, there was a higher rate of negative EPS under GA (28% GA versus 16% MAC, P =0.02), translating to a higher rate of nonablation (34% GA versus 14% MAC, P <0.001). In multivariable models, GA was associated with negative EPS in PVC/VT (odds ratio, 2.2 [95% CI, 1.1–4.4], P =0.03) but not in supraventricular tachycardia or ectopic atrial tachycardia. Acute ablation success was not different between strategies (94% GA versus 94% MAC, P =0.2). Major adverse events were rare, with no differences between GA and MAC. Conclusions: In this first report on pediatric ablation data in the Improving Pediatric and Adult Congenital Treatment Registry, there were no differences between GA and MAC in supraventricular tachycardia or ectopic atrial tachycardia inducibility, acute ablation success, or major adverse events. GA was associated with higher rates of noninducibility and nonablation in PVC/VT cases. A MAC strategy should be considered for PVC/VT ablation in the pediatric population. Abstract : Supplemental Digital Content is available in the text.